The Use of PopUp Book Media on the Material Structure and Function of Plants to Improve Student Learning Outcomes - Elidayani , Evi (International Journal of Science Education and Science, 2025)
This study aims to determine the use of pop up book media on the material structure and function of plants to improve student learning outcomes. The method used in this research is quantitative method with meta-analysis. using statistical data from various sources to obtain a data. The results of this study are that pop-up book media improves student learning outcomes in the material structure and function of plants by looking at the statistical data obtained there is an increase in student learning outcomes from 30% to 60%